When and how managerial ties and institutional distance matters for export venture performance in a digital age : an emerging market perspective : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Marketing at Massey University, Albany, New Zealand - Sima, Herbert (Massey University, 2022)
Despite the recent research on export performance, research is still unclear about what and how drives export performance in the digital age, especially for firms from emerging markets. Given the unprecedented and rapid environmental changes globally, exporting firms from emerging markets have encountered serious strategic issues. To overcome the challenges caused by cross-market institutional environment distance, social networking theory suggests that emerging market export firms need to rely on different managerial ties (host market business and political ties, home market ties and intrafirm ties) when conducting business in foreign host markets. Drawing on resource integration and innovation, social networking theory, digital technology, social media, institutional theory and export venture performance literature, in this thesis I have developed a series of conceptual models that have addressed the key research gaps in the extant literature. This thesis consists of three papers. Paper 1 is a conceptual study that outlines the contingent role of managerial ties in the resource integration-export venture innovation framework concerning emerging market export ventures. Paper 1 provides a platform for further empirical exploration, in relation to resource integration, managerial ties and export venture innovation. In Paper 2, I explore and examine the contingent effect of managerial ties in the digital market technology-export venture performance framework. In Paper 3, I further uncover the contingent effect of the institutional environment in the social media platform-export venture performance framework. The studies in Papers 2 and 3 are conducted based on the empirical evidence of 251 Chinese manufacturing firms’ export ventures. The results suggest that digital marketing technology has a direct impact on export venture economic and channel performance. In Paper 2, it is found that host market managerial ties (business and political) can positively impact the effect of digital marketing technology on export venture performance, whereas home market managerial ties either have no impact or have a negative contingent effect on digital marketing technology-export venture performance conceptualisation. In Paper 3, my research findings confirm that a firm’s social media platform has a direct and significant effect on export venture economic and channel performance. The institutional environment has both dark and bright side effects in the social media platform-export venture performance framework. Collectively my empirical research offers substantial new and novel insights into social networking theory, institutional theory, digital marketing technology, social media platform, and export venture literature. The outcomes of my research also provide insightful managerial implications for export ventures, especially for those from the emerging markets operating in foreign host markets.
Keywords: Export marketing; Developing countries; Management; Internet marketing; Social media; Marketing; managerial ties; export venture; economic and channel performance; institutional theory; marketing strategy; dark and bright side effect; digital marketing; social networking; home market managerial tie; host market managerial tie; innovation; resource integration; emerging market; social media platform; 350607 Marketing technology